2003
DOI: 10.1592/phco.23.6.754.32185
|View full text |Cite
|
Sign up to set email alerts
|

Safety of Antidepressant Drugs in the Patient with Cardiac Disease: A Review of the Literature

Abstract: Patients with cardiac disease, specifically ischemic heart disease and heart failure, have a higher frequency of major depressive disorder than patients without cardiac disease. The pathophysiologic reason for this is not completely understood. Previous depression, other debilitating illnesses, and type A personality are risk factors for the development of depression in cardiac patients. Depression has been shown to lower the threshold for ventricular arrhythmias. Therefore, treatment of depression potentially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
94
0
3

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 94 publications
2
94
0
3
Order By: Relevance
“…Data support that SSRIs decrease the serotonin-induced activation of platelets [43], but we do not know yet the clinical implication of this effect. Ziegelstein et al [60] demonstrated that patients with ACS, under SSRI treatment on top of conventional antiplatelet therapy, had a lower risk of myocardial ischemia, rise of cardiac enzymes and development of HF during hospitalization compared to those not receiving SSRIs, at the expense however of increased bleeding risk [60].…”
Section: • Underlying Biological Mechanismsmentioning
confidence: 85%
See 1 more Smart Citation
“…Data support that SSRIs decrease the serotonin-induced activation of platelets [43], but we do not know yet the clinical implication of this effect. Ziegelstein et al [60] demonstrated that patients with ACS, under SSRI treatment on top of conventional antiplatelet therapy, had a lower risk of myocardial ischemia, rise of cardiac enzymes and development of HF during hospitalization compared to those not receiving SSRIs, at the expense however of increased bleeding risk [60].…”
Section: • Underlying Biological Mechanismsmentioning
confidence: 85%
“…TCA overdose may trigger AV block, bundle branch block or ventricular arrhythmias. The Cardiac Arrhythmia Suppression Trial (CAST) [42] suggested that TCAs should be avoided in patients with cardiovascular disease (CVD) due to the risk of lifethreatening arrhythmias especially when co-prescribed with other drugs prolonging QT interval [43]. On the other hand SSRIs have lower risk of adverse anti-cholinergic and anti-histaminergic side effects [43].…”
Section: Safety Of Antidepressants In Cardiovascular Diseasementioning
confidence: 99%
“…Studies assessing SSRI efficacy in the treatment of depression in which resting effects on heart rate or blood pressure were also reported generally show either small or no effects of the SSRI on these cardiovascular parameters (Alvarez and Pickworth 2003;Amsterdam et al 1999;Glassman et al 2002). The reason for the relatively large differences observed in resting blood pressure and heart rates between the two treatment groups is unclear, although this could be potentially explained by the study conditions.…”
Section: Discussionmentioning
confidence: 98%
“…40 For example, SSRIs may decrease thrombotic events by reducing platelet activation. 41 Treatment with tricyclic antidepressants and SNRIs has been associated with decreased pro-inflammatory markers, when compared with treatment with SSRIs, which may slow progression of heart failure. 14 SSRIs are considered to be both efficacious and safe.…”
Section: Treatment Considerationsmentioning
confidence: 99%